The Relationship of Religious Development, Moral Values and Early Childhood Independence: Voices from Yogyakarta, Indonesia - Hibana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Religious moral values ​​are closely related to children's independence, but their development still requires intervention from teachers. Teachers in early childhood education play an important role because early childhood is the future of development and learning. This study aims to explain the relationship between the development of religious and moral values ​​with children's independence. The research was conducted at PAUD Terpadu Mutiara Yogyakarta. Simple random sampling technique was used in taking a sample of 48 participants. This research is a quantitative descriptive research using using techniques. The instrument in this study was a questionnaire on the development of religious and moral values ​​and a questionnaire for children's independence. Data were analyzed using the product moment. Results show that the level of religious and moral development values ​​of children in PAUD Terpadu Mutiara Yogyakarta was in the moderate or good category; the average score of the development variable of religious and moral values ​​of 77.08%. Meanwhile, the level of children's independence was moderate or good, which was shown by the child's average score of 93.75%.